Pelatihan Pembuatan Media Tangga Cerdas Untuk Meningkatkan Kreativitas Guru Di Desa Omo - Rabiatun Adwiah; Nurhikmah; Taufiqurrahman Usman; Nurlelah (Kilau Publishing, 2024)
Teacher creativity in designing innovative learning media is an important factor in improving the quality of education. Creative learning media can help students understand the material more easily and have fun. The aim of this community service activity is to provide training to teachers on how to create Smart Ladder media, in order to increase teacher creativity and make learning more interactive and effective. This training was attended by 8 teachers from SDN Omo. Community Service Procedures (PkM) are divided into 3 parts, namely planning, implementation, discussion and evaluation. The results of the training showed that the participants succeeded in creating intelligent ladder media that was appropriate to the subjects they taught. In addition, they also show an increased understanding of the importance of creativity in learning. It is hoped that the application of the Smart Ladder media can support the creation of more interesting learning, increase student understanding, and enrich the learning experience at school.